Age-Related Differences in Bimanual Isometric Force Tracking - Elisa Galofaro; Nicola Vale; Giulia Ballardini; Nicola Smania; Maura Casadio (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Bimanual force coordination is essential for activities of daily living. Although the age-related decline in sensorimotor function has been extensively studied, the effects of aging on the bilateral control of isometric forces remain less explored. This study used an isometric force tracking task to investigate bimanual force control in young and older adults. Participants were instructed to apply equal isometric force with both hands simultaneously by pushing against two decoupled plates, simulating the lateral faces of a box. The total force had to match a profile that included time-varying and constant phases, targeting three distinct force levels. Visual feedback of the total force was provided throughout the task. Thirty-one volunteers participated in the study: 16 younger adults of age $25± 1$ (mean±std) years and 15 older participants of age $77± 7$ years. Differences between the two groups were analyzed using mixed-design ANOVA, with the group as a between-subjects factor. Results indicated that older adults exhibited reduced between-hand force correlation and reduced bilateral symmetry than the younger participants. Additionally, the older group demonstrated lower accuracy and greater force variability, with these differences being more pronounced for the time-varying phases. Notably, the percentage of total force exerted by the left hand was negatively correlated with the disparity between the left and right coefficients of variation. This study confirms previous findings on the effect of aging on bimanual force control and provides evidence suggesting that the contribution of each hand may depend on the variability in force exertion.